Corn Grain Yield Trends from 2012 to 2016: A 26-Year Long-Term Experiment - J. Rivera-Zayas; Charles Rice (Kansas Agricultural Experiment Station Research Reports, 2017)
Long-term research trials provide an understanding of long-term effects on crop production. This long-term research studied the effect of conventional tillage (CT) and no-tillage (NT) systems. Factors of this 22-year study of corn (Zea maysL.) production also included the application of nitrogen (N) in the forms of ammonium nitrate and manure at rates of 150 lb/N/a. Corn grain yield trends during 2012 to 2016 were affected by the interaction between N source and year (P<0.05). The interaction between tillage practices and N source and the overall interaction between the last 5 years did not yield performance (P>0.05). Under the studied conditions the 75 lb/N/a as N fertilizer or manure achieved high corn yields.
Keywords: corn yield; nitrogen fertilizer; manure; till; no-till